2009
DOI: 10.1093/alcalc/agp049
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Acoustic Startle Responses and Seizure Thresholds between Ethanol-Withdrawn Male and Female Rats

Abstract: Observed sex differences in the startle reactivity during EW were consistent with earlier findings comparing EW seizure risk in male and female rats. Responses of OVX suggested that both hormones and differences in brain structures between males and females have a role in these sex differences. Our findings add weight to recommendations that treatment of alcohol withdrawal in humans should consider hormonal status as well as withdrawal time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
(38 reference statements)
5
23
1
Order By: Relevance
“…There are an increasing number of reports of significant and robust sex differences in recovery from the enhanced seizure risk of EW, in startle responses, as well as in responses to acute treatment with ethanol and neuroactive steroids (Alele and Devaud, 2007;Devaud and Chadda, 2001;Koirala et al, 2008;Reilly et al, 2009;Veatch et al, 2007). The present study extended Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…There are an increasing number of reports of significant and robust sex differences in recovery from the enhanced seizure risk of EW, in startle responses, as well as in responses to acute treatment with ethanol and neuroactive steroids (Alele and Devaud, 2007;Devaud and Chadda, 2001;Koirala et al, 2008;Reilly et al, 2009;Veatch et al, 2007). The present study extended Fig.…”
Section: Discussionsupporting
confidence: 68%
“…This correlates with findings of Deshmukh and colleagues (2003) that women show fewer and less severe EW symptoms than men, even when controlled for equivalent consumption. Behavioral assessments of withdrawal signs have also found sex differences in motor incoordination and acoustic startle responses (Reilly et al, 2009). We have also observed differential responsiveness to pharmacological challenges during EW between male and female rats (Alele and Devaud, 2007;Koirala et al, 2008).…”
supporting
confidence: 53%
“…Perhaps more relevant, male rats also showed greater motivational signs of withdrawal, such as anxiety-like responses in the social interaction test (Varlinskaya and Spear, 2004) and elevated plus maze after one cycle of exposure to a liquid diet (Overstreet et al, 2004). Males showed greater increases in acoustic startle responses than either intact female rats or ovariectomized female rats (Reilly et al, 2009), and males showed greater hangover-like anxiety-like responses (Varlinskaya and Spear, 2004). Chronic ethanol exposure/withdrawal results in modestly elevated ethanol intake in male HAP-2 mice.…”
Section: Sex Differences In Drug Abusementioning
confidence: 99%
“…Ethanol. From the perspective of actual signs and symptoms of withdrawal, males generally show a greater withdrawal response and slower recovery from acute alcohol withdrawal (Varlinskaya and Spear, 2004;Reilly et al, 2009;Carroll and Anker, 2010). For example, male rats, compared with females, that were withdrawn from alcohol had greater physical signs of withdrawal, such as greater seizure susceptibility (Devaud and Chadda, 2001).…”
Section: Sex Differences In Drug Abusementioning
confidence: 99%
“…Acoustic startle is also a common measure of anxiety-related effects of drug and alcohol withdrawal. Acoustic startle in rodents has been shown to be both increased (Chester, Blose, & Froehlich, 2003, 2004; Macey, Schulteis, Heinrichs, & Koob, 1996; Rassnick, Koob, & Geyer, 1992; Reilly, Koirala, & Devaud, 2009; Vandergriff, Kallman, & Rasmussen, 2000) and decreased (Chester & Barrenha, 2007; Chester et al, 2003; Chester, Blose, & Froehlich, 2005; Gilliam & Collins, 1986; Mejia-Toiber, Boutros, Markou, & Semenova, 2014) during the first 24–72 h in withdrawal from forced alcohol exposure. The differences in direction of the acoustic startle response during withdrawal in these studies are likely due to factors such as species and strain differences in alcohol sensitivity as well as dose and pattern of forced alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%